PERLINDUNGAN TOKOH PAK RADEN (SERIAL UNYIL) DALAM REZIM HAK CIPTA, MUNGKINKAH ? - Silky Yolanda Villincya (Institut Pendidikan Tapanuli Selatan, 2022)
A fictional character is a form of depiction of the character of a certain character that is poured into written or image form which is an important element in a story as well as Pak Raden's character in the Unyil series which is also a fictional character which of course has the essence to be protected. The purpose of this study itself is to examine more deeply whether a fictional character, in this case Mr. Raden in the Unyil series, can be granted copyright protection or vice versa. In achieving this goal, the Statute Approach is used, namely an approach to related regulations in this case the Copyright Law, Conceptual Approach is an approach that is carried out by examining the principles, opinions, and existing legal theories and the Comparative Approach. namely by comparing the regulations related to the issues faced by other countries, in this case the United States of America. Based on the provisions in the Copyright Act that a fictional character can be given protection in the event that it is manifested in a tangible form, while based on the standard thought put forward by the United States court, not all fictional characters can be granted copyright protection even though they have been realized in a tangible form.